Wearable electrolyte concentration sensor based on screen printing and preparation method thereof
Preparation of wearable electrolyte concentration sensors through the screen printing process and drip casting method, solve the problem of high cost and poor process flexibility in existing technology, realize low -cost and high -efficiency preparation methods, improve the manufacturing accuracy and performance stability of performance stability Essence
Patent Information
- Application Number
- CN202411943647.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-01-28
AI Technical Summary
The existing wearable electrolyte concentration sensor preparation methods are costly, poor process flexibility, insufficient printing accuracy and durability, and unclear process parameters relationship, resulting in low success rate.
The wire printing process and drip casting method preparation electrical chemical detection electrode and ion select the membrane layer. By targeting marking positioning, alignment and alignment to improve the accuracy of each layer, simplify the process process and reduce costs.
The preparation of low -cost, high -efficiency electrolyte concentration sensors is achieved, and the structure compactness and performance stability of the manufacturing accuracy and sensor are improved, and they are suitable for batch production.
Smart Images

Figure CN119375317A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biosensors, and in particular to a wearable electrolyte concentration sensor based on screen printing and a preparation method thereof. Background Art
[0002] The concentration of normal electrolytes plays a key role in maintaining the stability of osmotic pressure inside and outside human cells and acid-base balance. Electrolytes are essential for brain, nerve and muscle function and the formation of new tissues. If the human body lacks major electrolytes such as sodium, potassium and calcium, neurological diseases will occur. Especially for people who often exercise vigorously, sweat easily and sweat a lot, special attention should be paid to detecting electrolyte levels. Sweat and interstitial fluid of the human epidermis are ideal research objects for long-term, semi-continuous and non-aggressive health monitoring because it is a continuously available biofluid containing rich physiological and metabolic information. In recent years, wearable sensing technology for electrolyte concentration in human body fluids has attracted more and more attention and interest.
[0003] Compared with optical detection, colorimetric detection and other methods, the electrochemical detection method of electrolyte ions based on open circuit potential has unique advantages. Due to the portability of miniaturized and non-invasive sensors, advanced technologies for electronic and data transmission are analyzed and used mechanically. The potentiometric method, also known as the ion-selective electrode method, is a method that uses membrane electrodes to convert the activity of the measured ions into electrode potential for measurement. When measuring the concentration of ions, the potentiometric method measures the free ions in the solution, which does not destroy the equilibrium relationship in the solution. It is commonly used for the detection of sodium, calcium, potassium, chloride, ammonium, hydrogen and other ions. Therefore, it is very important to study wearable electrolyte concentration sensors and their preparation methods.
[0004] Existing research has explored wearable body fluid electrolyte concentration sensors and their preparation methods. Application No. CN202311384021.3 discloses a multi-parameter flexible / wearable sweat sensor and its preparation method. Four working electrodes, a pair of common counter electrodes and a reference electrode are integrated on the same flexible substrate to simultaneously detect glucose, lactate, sodium ions and potassium ions. The study used photolithography, wet etching and evaporation to prepare the working electrodes, which is costly and has low process flexibility. Application No. CN202280078323.5 discloses a system and method for a microfluidic biosensor patch and a health monitoring system, which includes an iontophoresis module, a multi-inlet microfluidic sweat collection and sampling module, and a molecular imprinted polymer (MIP) organic compound sensor module. The scheme uses laser engraving induced graphene technology to prepare electrochemical electrodes, and the processing technology is relatively simple, but it is limited to a few limited substrate materials such as polyimide and paper.
[0005] However, the current difficulties in developing wearable electrolyte concentration sensor preparation methods lie in the following aspects. First, the electrochemical electrodes prepared by photolithography, evaporation, inkjet printing and other methods are costly and have poor process flexibility. In comparison, screen printing is more convenient, but the current printing accuracy and durability are insufficient; secondly, the electrodes used for electrolyte concentration detection are often composed of a multi-layer structure. When screen-printing micro-scale electrodes, it is difficult to align the layers, which reduces the manufacturing accuracy; finally, the relationship between the process parameters such as ink concentration and printing motion used in the screen printing process has not yet been clarified, resulting in a very low success rate for electrode preparation. Summary of the invention
[0006] The object of the present invention is to provide a wearable electrolyte concentration sensor based on screen printing and a preparation method thereof, so as to solve the deficiencies in the prior art.
[0007] To achieve the above object, the present invention provides the following solutions: A method for preparing a wearable electrolyte concentration sensor based on screen printing comprises the following steps: S1, cleaning the surface of the flexible material substrate and drying it, screen-printing the shapes of the symmetrically arranged electrode substrate, wire substrate, electrical connection terminal and alignment mark on the flexible material substrate by silver ink, and heating and curing the silver ink; S2, aligning the reference electrode screen with an alignment mark in the flexible material substrate, screen-printing a reference electrode layer on the corresponding electrode substrate using silver / silver chloride ink, and heating and curing the silver / silver chloride ink; S3, aligning the working electrode screen with another alignment mark in the flexible material substrate, screen-printing a working electrode layer on the corresponding other electrode substrate using carbon ink, and heating and curing the carbon ink; S4, aligning the insulating layer screen with the two alignment marks in the flexible material substrate, screen-printing an insulating layer on the flexible material substrate using insulating ink, covering the outer surface of the conductor substrate, and curing the insulating ink by ultraviolet light; S5, preparing a protective film solution and an ion selective solution, and dropping the prepared protective film solution and ion selective solution onto the corresponding reference electrode layer and working electrode layer respectively by drop casting, and standing to solidify; S6. Cut the flexible material matrix by a cutting machine to obtain a wearable electrolyte concentration sensor.
[0008] Preferably, in step S1, the flexible material substrate is PET, and the flexible material substrate is cleaned by ultrasonic cleaning. The specific process is: anhydrous ethanol is selected as the cleaning medium, and then the flexible material substrate is ultrasonically cleaned for 5 to 10 minutes, and then dried at room temperature for 5 to 10 minutes.
[0009] Preferably, in step S1, the silver ink is a finished ink and does not need to be diluted with a diluent, and the process parameters controlled by the screen printing process in step S1 include ink concentration, plate movement rate and plate brushing pressure, the plate brushing rate is 159~179cm / min, the plate brushing pressure is 14~17N, and printing is repeated 3 times. After printing is completed, the entire flexible material substrate is dried in a high-temperature drying oven at 55°C for 5~20min.
[0010] Preferably, in step S2, the silver / silver chloride ink is a finished ink and does not need to be diluted with a diluent, and the process parameters controlled by the screen printing process in step S2 include ink concentration, plate movement rate and plate brushing pressure, the plate brushing movement rate is 159~179cm / min, the plate brushing pressure is 14~17N, and printing is repeated 3 times. After printing is completed, the entire flexible material substrate is dried in a high-temperature drying oven at 55°C for 5~20min.
[0011] Preferably, in step S3, carbon nanotubes are mixed in the carbon ink, and the mixing ratio of the carbon nanotubes to the carbon ink is 2.5% of the carbon nanotube content, and the process parameters controlled by the screen printing process in step S3 include ink concentration, brush plate movement rate and brush plate pressure, the solid content of the carbon ink is 33%~38%, the mixing ratio of the carbon ink and the diluent is 8%~10%, the brush plate movement rate is 159~179cm / min, and the brush plate pressure is 14~17N. The printing is repeated 3 times. After printing is completed, the flexible material substrate as a whole is dried in a high-temperature drying oven at 55°C for 5~20min.
[0012] Preferably, in step S4, the insulating ink is a finished ink and does not need to be diluted with a diluent, and the process parameters controlled by the screen printing process in step S4 include ink concentration, brush plate movement rate and brush plate pressure, the brush plate movement rate is 159~179cm / min, the brush plate pressure is 15~17N, the printing is repeated 3 times, and then the flexible material substrate is placed in an ultraviolet light environment as a whole for curing, the ultraviolet light power is 800W~1200W, and the curing time is 30s~50s.
[0013] Preferably, in step S5, the preparation process of the protective film solution is: 79.1 mg of PVB, 50 mg of NaCl and 2 mg of F127 are respectively dissolved in 1 ml of methanol solution to obtain a uniform protective film solution, and then the protective film solution is dripped onto the surface of the reference electrode layer by a drop casting method, and the drop casting volume of the protective film solution is 0.23 μL / mm 2 The surface area of the reference electrode layer was measured. After drop casting, it was placed in a 4°C environment and allowed to stand for 40 minutes to solidify.
[0014] Preferably, in step S5, the chemical composition of the prepared ion selective membrane solution is variable according to the different ion objects to be measured, so as to adapt to different ion selectivity requirements.
[0015] The present invention also provides a wearable electrolyte concentration sensor prepared by the above-mentioned preparation method, comprising a flexible material substrate, a reference electrode layer and a working electrode layer, wherein an integrated electrode assembly is symmetrically arranged on the flexible material substrate, and the two integrated electrode assemblies are both composed of an electrode substrate, a wire substrate and an electrical connection end connected in an integrated manner; The reference electrode layer is arranged on an electrode substrate, and the material is silver / silver chloride, and a protective film layer is arranged on the electrode substrate, and the protective film layer is a polyvinyl alcohol butyral layer saturated with NaCl; The working electrode layer is arranged on another electrode substrate, made of carbon, and covered with carbon nanotubes on the surface, and an ion selective membrane layer is arranged above the working electrode layer for identifying the electrolyte ions to be measured in the body fluid sample; The outer surface of the conductor substrate is covered with an insulating layer, which is used to achieve an electrical insulation state between the conductor substrate and the external environment.
[0016] According to the specific embodiments provided by the present invention, the present invention discloses the following technical effects: (1) The present invention adopts screen printing and drop casting to prepare electrochemical detection electrodes and ion selective membrane layers, avoiding the use of processes such as photolithography, reducing costs while improving detection efficiency; and in the process of printing each layer of material, alignment marks are used for positioning and alignment, thereby improving the alignment accuracy of the diameter of each layer of graphics.
[0017] (2) The preparation method provided by the present invention is simple and has high manufacturing precision, and can be mass-produced. In addition, the electrolyte concentration sensor has a compact structure and stable performance, and can effectively monitor the electrolyte concentration in body fluid samples, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0019] Figure 1 This is a flow chart of a method for preparing a wearable electrolyte concentration sensor based on screen printing according to the present invention; Figure 2 Schematic diagram of the structure of the wearable electrolyte concentration sensor of the present invention; Description of reference numerals: 1. Electrolyte concentration sensor; 100. Flexible material substrate; 101. Electrode substrate; 102. Wire substrate; 103. Electrical connection terminal; 104. Reference electrode layer; 105. Protective film layer; 106. Working electrode layer; 107. Ion selective membrane layer; 108. Insulating layer. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the present invention is further described in detail below with reference to the accompanying drawings.
[0022] like Figure 1 As shown, the present invention provides a method for preparing a wearable electrolyte concentration sensor based on screen printing, comprising the following steps: S1, cleaning the surface of the flexible material substrate and drying it, screen-printing the shapes of the symmetrically arranged electrode substrate, wire substrate, electrical connection terminal and alignment mark on the flexible material substrate by silver ink, and heating and curing the silver ink; S2, aligning the reference electrode screen with an alignment mark in the flexible material substrate, screen-printing a reference electrode layer on the corresponding electrode substrate using silver / silver chloride ink, and heating and curing the silver / silver chloride ink; S3, aligning the working electrode screen with another alignment mark in the flexible material substrate, screen-printing a working electrode layer on the corresponding other electrode substrate using carbon ink, and heating and curing the carbon ink; S4, aligning the insulating layer screen with the two alignment marks in the flexible material substrate, screen-printing an insulating layer on the flexible material substrate using insulating ink, covering the outer surface of the conductor substrate, and curing the insulating ink by ultraviolet light; S5, preparing a protective film solution and an ion selective solution, and dropping the prepared protective film solution and ion selective solution onto the corresponding reference electrode layer and working electrode layer respectively by drop casting, and standing to solidify; S6. Cut the flexible material matrix by a cutting machine to obtain a wearable electrolyte concentration sensor.
[0023] In the above step S1, the flexible material substrate is PET, and the flexible material substrate is cleaned by ultrasound. The specific process is: anhydrous ethanol is selected as the cleaning medium, and then the flexible material substrate is washed by ultrasonic oscillation for 5 to 10 minutes, preferably 5 minutes, and then dried at room temperature for 5 to 10 minutes, preferably 5 minutes. After drying, screen printing is performed. Silver ink is used to print the electrode substrate, the wire substrate and the electrical connection end. In addition, the silver ink is a finished ink and does not need to be diluted with a diluent. The process parameters controlled by the screen printing process in step S1 include ink concentration, plate movement rate and plate pressure. The plate movement rate is 159 to 179 cm / min, preferably 169 cm / min; the plate pressure is 14 to 17 N, preferably 15 N; the printing is repeated 3 times, and after printing, the flexible material substrate is dried as a whole in a high-temperature drying oven at 55°C for 5 to 20 minutes, preferably 15 minutes.
[0024] In the above step S2, on the basis of printing the electrode substrate, the wire substrate, the electrical connection end and the alignment mark on the PET flexible material substrate, the alignment mark on the flexible material substrate is taken as the object, and the alignment mark on the reference electrode screen is passed through the alignment mark on the reference electrode screen to align the reference electrode screen and the alignment mark on the flexible material substrate, and then the reference electrode layer is printed with silver / silver chloride ink. The silver / silver chloride ink is a finished ink and does not need to be diluted with a diluent, and the process parameters controlled by the screen printing process in step S2 include ink concentration, brush plate movement rate and brush plate pressure, the brush plate movement rate is 159~179cm / min, preferably 169cm / min; the brush plate pressure is 14~17N, preferably 15N; the printing is repeated 3 times, and after the printing is completed, the flexible material substrate is dried as a whole in a high-temperature drying oven at 55°C for 5~20min, preferably 15min.
[0025] In the above step S3, on the basis of printing the electrode substrate, the wire substrate, the electrical connection end and the alignment mark on the PET flexible material substrate, the alignment mark on the flexible material substrate is taken as the object, and the alignment mark on the working electrode stencil is passed through the alignment mark on the working electrode stencil to align the alignment mark on the working electrode stencil and the flexible material substrate, and then the working electrode layer is printed using carbon ink mixed with carbon nanotubes. The mixing ratio of carbon nanotubes and carbon ink is 2.5% of the carbon nanotube content, and the process parameters controlled by the screen printing process in step S3 include ink concentration, brush plate movement rate and brush plate pressure, the solid content of carbon ink is 33%~38%, preferably 35%; the mixing ratio of carbon ink and diluent is 8%~10%, preferably 10%; the brush plate movement rate is 159~179cm / min, 169cm / min; the brush plate pressure is 14~17N, preferably 15N; the printing is repeated 3 times, and after the printing is completed, the flexible material substrate is dried in a high temperature drying oven at 55°C for 5~20min, preferably 15min.
[0026] In the above step S4, on the basis of printing the electrode substrate, the wire substrate, the electrical connection end and the alignment mark on the PET flexible material substrate, the alignment mark on the flexible material substrate is taken as the object, and the alignment mark on the insulating layer screen is passed through the alignment mark on the insulating layer screen to align the insulating layer screen and the alignment mark on the flexible material substrate, and then the insulating layer is printed with insulating ink. The insulating ink is a finished ink and does not need to be diluted with a diluent, and the process parameters controlled by the screen printing process in step S4 include ink concentration, brush plate movement rate and brush plate pressure, the brush plate movement rate is 159~179cm / min, preferably 169cm / min; the brush plate pressure is 15~17N, preferably 16N; repeat printing 3 times, and then place the flexible material substrate as a whole in an ultraviolet light environment for curing, the ultraviolet light power is 800W~1200W, preferably 1000W; the curing time is 30s~50s, preferably 40s.
[0027] In the above step S5, the preparation process of the protective film solution is as follows: 79.1 mg of PVB, 50 mg of NaCl and 2 mg of F127 are respectively dissolved in 1 ml of methanol solution to obtain a uniform protective film solution, and then the protective film solution is dripped onto the surface of the reference electrode layer by a drop casting method. The drop casting volume of the protective film solution is 0.23 μL / mm 2 The surface area of the reference electrode layer was measured. After drop casting, it was placed in a 4°C environment and allowed to stand for 40 minutes to solidify.
[0028] In addition, in the above step S5, the chemical composition of the prepared ion selective membrane solution is variable according to the different ion objects to be detected to adapt to different ion selectivity requirements. Here, the detection of sodium, calcium, potassium, chloride, ammonium, hydrogen and other ions is described. For the sodium ion selective membrane, the chemical reagents and their proportions are added to 1mL of tetrahydrofuran (THF) solution, 1%wt of sodium ion carrier, 0.5% of Na-TFPB, 65.5% of dioctyl sebacate (DOS) and 33% of polyvinyl chloride (PVC). For the calcium ion selective membrane, the chemical reagents and their proportions are 2wt% of ETH129, 1wt% of Na-TFPB, 130.9wt% of DOS and 66wt% of PVC are dissolved in 1320μL of THF respectively. For the chloride ion selective membrane, the chemical reagents and their proportions are 100mg of PVC:O-NPOE in a ratio of 34:51:15wt% is dissolved in 1.0mL of THF. For potassium ion selective membrane, the chemical reagents and their proportions are 200 mg of membrane components containing 1 wt% valinomycin, 0.4 wt% KTFPB, 32.9 wt% PVC and 65.7 wt% DOS dissolved in 2 mL THF. For ammonium ion selective membrane, the chemical reagents and their proportions are 50% dibutyl phthalate + 0.75% potassium tetra(4-chlorophenyl)borate + 1.20% inactive bacterin, the mass ratio of the base PVC to dibutyl phthalate is 1:1, and the mass ratio with the solvent THF is 1:20. For hydrogen ion selective membrane, the chemical reagents and their proportions are 1% by mass TDDA, 0.6% KTPB, 65.6% DOS and 32.8% PVC dissolved in THF.
[0029] Reference Figure 2The wearable electrolyte concentration sensor 1 prepared by the above-mentioned preparation method includes a flexible material substrate 100, a reference electrode layer 104 and a working electrode layer 106. The flexible material substrate 100 is symmetrically provided with integrated electrode assemblies, and the two integrated electrode assemblies are both composed of an electrode substrate 101, a wire substrate 102 and an electrical connection end 103 connected in an integrated manner, wherein the electrode substrate 101, the wire substrate 102 and the electrical connection end 103 can be made of a material with high conductivity, preferably silver; the reference electrode layer 104 is arranged on an electrode substrate 101, and the material is silver / silver chloride, and a protective film layer 105 is arranged above it, and the protective film layer 105 is a polyvinyl alcohol butyral layer containing saturated NaCl, Used to maintain a stable electric potential without being disturbed by ions; a working electrode layer 106 is arranged on another electrode substrate 101, and is made of carbon and covered with carbon nanotubes on the surface to increase the surface area and improve the conductivity. An ion selective membrane layer 107 is arranged above the working electrode layer 106 to identify the electrolyte ions to be measured in the body fluid sample. Depending on the different ions to be measured, the chemical composition of the ion selective membrane used is different, and it is mainly suitable for the detection of sodium, calcium, potassium, chlorine, ammonium, hydrogen and other ions; the outer surface of the wire substrate 102 is covered with an insulating layer 108 to achieve an electrical insulation state between the wire substrate and the external environment. It should be noted that the insulating layer 108 does not cover the surface of the electrode substrate 101 and the electrical connection end 103.
[0030] The present invention is further described below through a specific implementation method.
[0031] Embodiment 1 In this embodiment, the method for preparing a wearable electrolyte concentration sensor based on screen printing includes the following steps: (1) PET is used as the flexible material substrate. When ultrasonically cleaning the flexible material substrate, anhydrous ethanol is used as the cleaning medium. The substrate is ultrasonically cleaned for 5 minutes and dried at room temperature for 5 minutes. After drying, silver ink is used to print the electrode substrate, the conductor substrate and the electrical connection terminal. During the printing process, the main process parameters to be controlled are ink concentration, plate movement speed, plate pressure and so on. Among them, the solid content of the ink is 61%; the plate movement speed is 169cm / min; the plate pressure is 15N, and the printing is repeated 3 times. After printing, the flexible substrate is placed in a high-temperature drying oven as a whole and dried at a temperature of 55°C for 15 minutes.
[0032] (2) Using the alignment mark on the flexible material substrate as the object, align the reference electrode screen and the mark on the flexible material substrate. Use silver / silver chloride ink to print the reference electrode layer. The solid content of the ink is 65%; the brush movement rate is 169cm / min; the brush pressure is 15N, and the printing is repeated 3 times. After printing, the flexible material substrate is placed in a high-temperature drying oven and dried at a temperature of 55°C for 15 minutes.
[0033] (3) Using the alignment mark on the flexible material substrate as the object, align the working electrode screen and the mark on the flexible material substrate. The working electrode layer is printed with carbon ink mixed with carbon nanotubes, and the mixing ratio of carbon nanotubes and carbon ink is 2.5. During the printing process, the solid content of the ink is 35%, and the mixing ratio with the diluent is 10%; the brush movement is 169cm / min; the brush pressure is 15N, and the printing is repeated 3 times. After printing, the flexible material substrate is placed in a high-temperature drying oven as a whole and dried at a temperature of 55°C for 15 minutes.
[0034] (4) Using the alignment mark on the flexible material substrate as the object, align the insulating layer screen and the mark on the flexible material substrate. Use insulating ink to print the insulating layer. The solid content of the ink is 100%; the brush plate moving speed is 169cm / min; the brush plate pressure is 16N, and the printing is repeated 3 times. After printing, the flexible material substrate is placed in an ultraviolet light environment with an ultraviolet light power of 1000w and a curing time of 40s.
[0035] (5) The chemical reagents and their proportions for preparing the protective film solution are as follows: 79.1 mg of PVB, 50 mg of NaCl, and 2 mg of F127 are dissolved in 1 mL of methanol, 1.5 μL of the solution is dropped on the surface of the reference electrode layer by drop casting; the solution is allowed to stand for 40 minutes at 4°C to solidify; (6) The chemical reagents and their proportions for preparing the sodium ion selective membrane solution are as follows: in 1 mL of sodium tetrafluoride solution, add 1%wt of sodium ion carrier, 0.5% of Na-TFPB, 65.5% of DOS and 33% of PVC, take 4.5 μL and drop it on the surface of the working electrode layer by drop casting; let it stand for 40 minutes in an environment of 4°C to solidify; (7) Finally, the flexible substrate is cut by a cutting machine to obtain a wearable sodium ion concentration sensor.
[0036] The invention further illustrates the use of the above-mentioned wearable electrolyte concentration sensor based on screen printing and its preparation method. The electrochemical detection electrode and ion selective membrane layer are prepared by screen printing process and drop casting method, avoiding the use of processes such as photolithography, reducing costs and improving detection efficiency. In addition, in the process of printing each layer of material, alignment marks are used for positioning and alignment, thereby improving the alignment accuracy of the diameter of each layer of graphics. In addition, the preparation method provided is simple and has high manufacturing precision, and can realize mass production. The electrolyte concentration sensor has a compact structure and stable performance, and can effectively monitor the electrolyte concentration in body fluid samples, and has broad application prospects.
[0037] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the system disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0038] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of the present invention. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A method for preparing a wearable electrolyte concentration sensor based on screen printing, characterized in that: The following steps are involved: S1, cleaning the surface of the flexible material substrate and drying it, screen-printing the shapes of the symmetrically arranged electrode substrate, wire substrate, electrical connection terminal and alignment mark on the flexible material substrate by silver ink, and heating and curing the silver ink; S2, aligning the reference electrode screen with an alignment mark in the flexible material substrate, screen-printing a reference electrode layer on the corresponding electrode substrate using silver / silver chloride ink, and heating and curing the silver / silver chloride ink; S3, aligning the working electrode screen with another alignment mark in the flexible material substrate, screen-printing a working electrode layer on the corresponding other electrode substrate using carbon ink, and heating and curing the carbon ink; S4, aligning the insulating layer screen with the two alignment marks in the flexible material substrate, screen-printing an insulating layer on the flexible material substrate using insulating ink, covering the outer surface of the conductor substrate, and curing the insulating ink by ultraviolet light; S5, preparing a protective film solution and an ion selective solution, and dropping the prepared protective film solution and ion selective solution onto the corresponding reference electrode layer and working electrode layer respectively by drop casting, and standing to solidify; S6. Cut the flexible material matrix by a cutting machine to obtain a wearable electrolyte concentration sensor.
2. The method for preparing a wearable electrolyte concentration sensor based on screen printing according to claim 1, characterized in that: In step S1, the flexible material substrate is PET, and the flexible material substrate is cleaned by ultrasonic cleaning. The specific process is: anhydrous ethanol is selected as the cleaning medium, and then the flexible material substrate is cleaned by ultrasonic oscillation for 5 to 10 minutes, and then dried at room temperature for 5 to 10 minutes.
3. The method for preparing a wearable electrolyte concentration sensor based on screen printing according to claim 2, characterized in that: In step S1, the silver ink is a finished ink and does not need to be diluted with a diluent. The process parameters controlled by the screen printing process in step S1 include ink concentration, brush plate movement rate and brush plate pressure. The brush plate movement rate is 159~179cm / min, and the brush plate pressure is 14~17N. The printing is repeated 3 times. After printing is completed, the entire flexible material substrate is dried in a high-temperature drying oven at 55°C for 5~20min.
4. The method for preparing a wearable electrolyte concentration sensor based on screen printing according to claim 1, characterized in that: In step S2, the silver / silver chloride ink is a finished ink and does not need to be diluted with a diluent. The process parameters controlled by the screen printing process in step S2 include ink concentration, brush plate movement rate and brush plate pressure. The brush plate movement rate is 159~179cm / min, and the brush plate pressure is 14~17N. Printing is repeated 3 times. After printing is completed, the entire flexible material substrate is dried in a high-temperature drying oven at 55°C for 5~20min.
5. The method for preparing a wearable electrolyte concentration sensor based on screen printing according to claim 1, characterized in that: In step S3, carbon nanotubes are mixed in the carbon ink, and the mixing ratio of the carbon nanotubes to the carbon ink is 2.5% of the carbon nanotube content, and the process parameters controlled by the screen printing process in step S3 include ink concentration, brush plate movement rate and brush plate pressure, the solid content of the carbon ink is 33%~38%, the mixing ratio of the carbon ink to the diluent is 8%~10%, the brush plate movement rate is 159~179cm / min, and the brush plate pressure is 14~17N. The printing is repeated 3 times. After printing is completed, the entire flexible material substrate is dried in a high-temperature drying oven at 55°C for 5~20min.
6. The method for preparing a wearable electrolyte concentration sensor based on screen printing according to claim 1, characterized in that: In step S4, the insulating ink is a finished ink and does not need to be diluted with a diluent. The process parameters controlled by the screen printing process in step S4 include ink concentration, brush plate movement rate and brush plate pressure. The brush plate movement rate is 159~179cm / min, and the brush plate pressure is 15~17N. The printing is repeated 3 times, and then the flexible material substrate is placed in an ultraviolet light environment for curing. The ultraviolet light power is 800W~1200W, and the curing time is 30s~50s.
7. The method for preparing a wearable electrolyte concentration sensor based on screen printing according to claim 1, characterized in that: In step S5, the preparation process of the protective film solution is as follows: 79.1 mg of PVB, 50 mg of NaCl and 2 mg of F127 are respectively dissolved in 1 ml of methanol solution to obtain a uniform protective film solution, and then the protective film solution is dripped onto the surface of the reference electrode layer by a drop casting method. The drop casting volume of the protective film solution is 0.23 μL / mm 2 The surface area of the reference electrode layer was measured. After drop casting, it was placed in a 4°C environment and allowed to stand for 40 minutes to solidify.
8. The method for preparing a wearable electrolyte concentration sensor based on screen printing according to claim 7, characterized in that: In step S5, the chemical composition of the prepared ion selective membrane solution is variable according to the different ion objects to be measured, so as to adapt to different ion selectivity requirements.
9. A wearable electrolyte concentration sensor prepared by the method for preparing a wearable electrolyte concentration sensor based on screen printing according to any one of claims 1 to 8, characterized in that: It comprises a flexible material substrate, a reference electrode layer and a working electrode layer, wherein the flexible material substrate is symmetrically provided with an integrated electrode assembly, and the two integrated electrode assemblies are both integrally formed by connecting an electrode substrate, a wire substrate and an electrical connection end; The reference electrode layer is arranged on an electrode substrate, and the material is silver / silver chloride, and a protective film layer is arranged on the electrode substrate, and the protective film layer is a polyvinyl alcohol butyral layer saturated with NaCl; The working electrode layer is arranged on another electrode substrate, made of carbon, and covered with carbon nanotubes on the surface, and an ion selective membrane layer is arranged above the working electrode layer for identifying the electrolyte ions to be measured in the body fluid sample; The outer surface of the conductor substrate is covered with an insulating layer, which is used to achieve an electrical insulation state between the conductor substrate and the external environment.
Citation Information
Patent Citations
Multi-parameter flexible / wearable sweat sensor and preparation method thereof
CN117405751A
Non-invasive method and apparatus for continuous sweat induction and collection
CN118401170A
Enzyme biosensor for detecting cholesterol as well as preparation method and application thereof
CN108776163A
Screen printing method and preparation method of flexible printed circuit board and flexible printed circuit board
CN111642079A
High-stability flexible sodium ion sensor and preparation method thereof
CN116359307A
Cited By
Portable flexible photoelectrochemical detector device
CN122409801A